ANTIOXIDANT AND ANTI-INFLAMMATORY PROPERTIES OF A SERIES OF NEW7,8-DISUBSTITUTED THEOPHYLLINE CONTAINING A PYRAZOLE RING - КОRОBKО DMYTRO; J. Hadjipavlou-litina, Dimitra; LOGOYDA, LILIYA (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The objective of this study was to synthesize methyl 1-(1,3-dimethyl-2,6-dioxo-7-arylalkyl-(alkenyl-)-2,3,6,7-tetrahydro-1H-purin-8-yl)- 5-(4-methyl-(methoxy-, chloro-)phenyl)-1H-pyrazole-3-carboxylates and studying their antioxidant and anti-inflammatory properties by in vitro methods. Methods: New derivatives of 1,3-dimethylxanthine with pyrazole at position 8 were synthesized by the interaction of 8-bromotheophylline with arylalkyl-(alkenyl) halides, hydrazine hydrate, and methyl 4-(4-R)-2,4-dioxobutanoate. For most obtained compounds, antioxidant activity (by 2,2-diphenyl-1-picrylhydrazyl and 2,2'-azobis(2-amidinopropane) dihydrochloride) and anti-inflammatory (by Soybean LOX inhibition) activity was investigated. Result: The most effect on free radical oxidation processes was recorded for substances with a phenylalyl radical at position 7 of the molecules (10, 13, and 16). In the activity of inhibition of peroxidation of lipids (89–92%), they predominate Trolox (88%). Their IC50 indices for LOX inhibition are 15.0, 17.5, and 27.5 μM, respectively, but less than the nordihydroguaretic acid reference compound used. Conclusion: The antioxidant and anti-inflammatory properties of a series of synthesized 7,8-disubstituted theophylline containing the pyrazole cycle have been studied using modern in vitro research methods. The prospect of conducting further synthetic and pharmacological studies for compounds with phenylalyl radical in the 7 positions of their molecules is shown.